2019
DOI: 10.1111/phpp.12480
|View full text |Cite
|
Sign up to set email alerts
|

Online sunscreen purchases: Impact of product characteristics and marketing claims

Abstract: Background Sunscreens, unlike prescription medications, are purchased by consumers directly from retailers. The proportion of online sunscreen sales is increasing. It is therefore important for dermatologists to know what factors influence online sunscreen purchases to optimize appropriate recommendations. Methods Data on the top 100 best‐selling sunscreens from an online retailer were collected. Variables included cost, formulation, product claims, ingredients, consumer ratings, and number of reviews. Ordinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 14 publications
2
10
0
Order By: Relevance
“…This has shown that there are product claims which are not regulated by the Food & Drug Administration (such as "non-greasy") in 57.3% of the sunscreen products they examined. 20 In concordance with the results of our study, this indicates that worldwide online marketing is not tightly regulated, despite the significantly better rates of marketing compliance by the USA in our data.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This has shown that there are product claims which are not regulated by the Food & Drug Administration (such as "non-greasy") in 57.3% of the sunscreen products they examined. 20 In concordance with the results of our study, this indicates that worldwide online marketing is not tightly regulated, despite the significantly better rates of marketing compliance by the USA in our data.…”
Section: Discussionsupporting
confidence: 92%
“…A recent American study by Prado et al have explored the factors influencing online sunscreen purchases by assessing labelling claims on the 100 best‐selling sunscreens in August 2018. This has shown that there are product claims which are not regulated by the Food & Drug Administration (such as “non‐greasy”) in 57.3% of the sunscreen products they examined 20 . In concordance with the results of our study, this indicates that worldwide online marketing is not tightly regulated, despite the significantly better rates of marketing compliance by the USA in our data.…”
Section: Discussionsupporting
confidence: 89%
“…Only a limited number of published studies explore sunscreen user preferences, primarily examining online retail sales. Prado, Ederle, et al (2019) looked at the top 100 best‐selling sunscreens on http://Amazon.com and found that a high number of total reviews and the presence of six or more unregulated marketing claims (e.g., “non‐greasy” or “fragrance‐free”) were the only factors correlated with higher online sales. Xu et al (2016) analyzed product reviews of top‐rated sunscreens on http://Amazon.com to determine what factors were most frequently mentioned as positive or negative features of the sunscreens.…”
Section: Considerations Relating To the Use Of Sunscreen Ingredient B...mentioning
confidence: 99%
“…The law prohibits sales of “chemical sunscreen” products that include these two UV filters in the state, but these products can be brought in when traveling or purchased online [ 6 ]. While there are numerous available UV filters [ 10 ], oxybenzone is one of the few filters that blocks most UVA (ultraviolet A) and UVB (ultraviolet B) radiation, and it is used in products that consumers tend to rate most highly [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%